The complete sequence of chloroplast genome of Baeckea frutescens Linaeus 1753 (Myrtoideae), a traditional folk medicinal plant - Chengcheng Ling; Menglei Zhang; Wenwen Ma; Menyu Liu (Mitochondrial DNA. Part B. Resources)
Baeckea frutescens Linaeus 1753, as a traditional folk medicine in South East Asia, possesses sesquiterpenes, phloroglucinols, chromones, and essential oil, and is utilized for traditional Chinese medicinal purposes. The genetic diversity of the plant must be better understood, considering its significance. The complete chloroplast (cp) genome of B. frutescens was sequenced and assembled by using Illumina paired-end data, marking a significant advancement toward comprehending its genetic composition. The complete cp genome is 158,939 bp in length and contains 128 genes, consisting of 83 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. Phylogenetic analyses indicated that B. frutescens and other the 13 were clustered to the family of Myrtaceae. These findings are crucial for the conservation and utilization of this important plant species. Additionally, they underscore the potential for future research on the evolution and preservation of B. frutescens, which could be advantageous in pharmaceutical applications.